Structural Variability of R2C Adducts of 3a, 6a‐Diaza‐1, 4‐diphosphapentalene: Tuning the N→P Bonding. Issue 19 (19th September 2017) - Kornev, Alexander N.; Galperin, Vadim E.; Panova, Yulia S.; Arapova, Alla V.; Baranov, Evgenii V.; Fukin, Georgy K.; Abakumov, Gleb A.
Abstract : 3a, 6a‐Diaza‐1, 4‐diphosphapentalene (DDP) reacts with hexachlorocyclopentadiene to form a stable adduct (ClC)4 C=DDP (4 ). The phosphorus atom involved into coordination has a pyramidal arrangement but retains partial double bonding with carbon [1.752(3) Å]. At the same time, the P–N bond remains covalent [1.824(3) Å]. The adduct4 is better described as a zwitterionic compound with strongly delocalized positive and negative charges. A similar zwitterionic adduct DDP=C(CN)2 was prepared by the reactions of dichloro‐DDP (7 ) with malononitrile in the presence of Et3 N. DFT calculations showed that related structures are formed in the case of the substituents (ClC)4 C=, (HC)4 C=, (NC)2 C=, and (MeCO)2 C=, possessing electron‐delocalizing properties. Compounds with other R 2 C groups ( R = Ph, Me, C6 F5, Cl), possessing electronegative properties as well, but insufficient e‐delocalization, demonstrate the noncovalent P–N bonding and a little shorter R 2 C–P bond lengths (ca. 1.70 Å). Abstract :